[LB.01.28] PREVALENCE OF HYPERTENSION AMONG CHINESE CHILDREN: A CROSS-SECTIONAL SURVEY. (September 2017) - Fan, H.; Yan, Y.; Mi, J.
Abstract : Objective: It was recommended that the diagnosis of childhood hypertension should be established on three separate occasions. The prevalence of childhood hypertension remains unknown in China. The goal of our study was to determine the prevalence of childhood hypertension in China, and examined the association between weight status and hypertension. Design and method: Data were obtained from a sample of 45262 Chinese children aged 6–17 years. Initial measurements included three oscillometric blood pressure (BP) readings. Children with elevated BP were screened a second or third time at 10-week intervals. Hypertension was defined as persistently elevated BP on all three occasions. Normal weight, overweight and obesity were evaluated based on age- and sex-specific BMI percentiles as recommended by the International Obesity Task Force. Logistical regression model was used to assess the association between weight status and hypertension after controlling for sex, age and other covariates. Results: The prevalence of elevated BP decreased across visits, from 16.9% during the first visit to 4.2% during the third visit. The prevalence of childhood hypertension was also 4.2%. Isolated systolic hypertension was the most frequent subtype of childhood hypertension. In addition, compared to children with normal weight, children with overweight or obesity were more likely to have hypertension. Conclusions: Childhood hypertension has been an emerging public-health problem in China. Our findings emphasized the importance of maintaining healthy weight in the prevention of childhood hypertension.